Rural Communities and Water Governance: Understanding Participatory Processes for Catchment Management in the Upper Umzimvubu Catchment - MBELE, Siyasanga; MUBANGIZI, Betty C (PT Keberlanjutan Strategis Indonesia, 2023)
Water is a crucial issue for sustainable livelihoods, and a lack of it impacts human life. Catchment areas play an essential role in water provisioning, and their management is fundamental for sustained water availability. The UN-endorsed Integrated Water Resources Management (IWRM) approach best expresses catchment management ideals that resonate with South Africa's constitutional ideals of efficient and equitable distribution of resources. South Africa has a history of inequality that led to severe neglect of rural areas in many facets, including the water sector. Despite the country's reformed laws and policies, sustainable water provision and access remain challenging, particularly in rural-based municipalities where land degradation and a weak revenue base interact to reduce access to water for most communities. This paper reports on a study that sought to understand participatory processes for catchment management in the upper Umzimvubu catchment within Matatiele Local Municipality in the Alfred Nzo District Municipality in the Eastern Cape Province. This study used a qualitative approach to data collection and document analysis. The findings show that participatory water governance strategies exist and tend to coalesce around non-governmental structures. The findings also show that there is room for improving water governance in rural communities, including the need to finalize the establishment of Catchments Management Areas (CMAs) in all nine existing Water Management Areas (WMAs) while incorporating strong community involvement and strengthening the capacity of rural municipalities.